Selection of binding targets in parasites using phage-display and aptamer libraries in vivo and in vitro - Tonelli, R. R. (Frontiers Media S.A., 2013)
Parasite infections are largely dependent on interactions between pathogen and different host cell populations to guarantee a successful infectious process. This is particularly true for obligatory intracellular parasites as Plasmodium, Toxoplasma, and Leishmania, to name a few. Adhesion to and entry into the cell are essential steps requiring specific parasite and host cell molecules. The large amount of possible involved molecules poses additional difficulties for their identification by the classical biochemical approaches. In this respect, the search for alternative techniques should be pursued. Among them two powerful methodologies can be employed, both relying upon the construction of highly diverse combinatorial libraries of peptides or oligonucleotides that randomly bind with high affinity to targets on the cell surface and are selectively displaced by putative ligands. These are, respectively, the peptide-based phage display and the oligonucleotide-based aptamer techniques. The phage display technique has been extensively employed for the identification of novel ligands in vitro and in vivo in different areas such as cancer, vaccine development, and epitope mapping. Particularly, phage display has been employed in the investigation of pathogen–host interactions. Although this methodology has been used for some parasites with encouraging results, in trypanosomatids its use is, as yet, scanty. RNA and DNA aptamers, developed by the SELEX process (Systematic Evolution of Ligands by Exponential Enrichment), were described over two decades ago and since then contributed to a large number of structured nucleic acids for diagnostic or therapeutic purposes or for the understanding of the cell biology. Similarly to the phage display technique scarce use of the SELEX process has been used in the probing of parasite–host interaction. In this review, an overall survey on the use of both phage display and aptamer technologies in different pathogenic organisms will be discussed. Using these techniques, recent results on the interaction of Trypanosoma cruzi with the host will be highlighted focusing on members of the 85 kDa protein family, a subset of the gp85/TS superfamily.